DIDO HUBUNGAN SELF CONFIDENCE DENGAN KEPUTUSAN KARIR PESERTA DIDIK SMKN 2 PADANG: HUBUNGAN SELF CONFIDENCE DENGAN KEPUTUSAN KARIR PESERTA DIDIK SMKN 2 PADANG - Suganda, Dido; Dianto, Mori; Chandra, Yasrial (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the phenomenon in the field where there are still students who do not show initiative in seeking additional information about careers and students who lack confidence in their own abilities. The objectives of this research are 1) to provide an overview of the self-confidence of students at SMKN 2 Padang, 2) to provide an overview of the career decisions of students at SMKN 2 Padang, and 3) to examine the relationship between students' self-confidence and their career decisions at SMKN 2 Padang. The research method uses a quantitative approach. The type of research used is correlational with a population of 161 eleventh-grade students, and a sample of 84 students thru simple random sampling. The instrument used in this study was a questionnaire with indicators of self-confidence and career decisions. The results of this study show: 1) The self-confidence of 11th-grade students at SMKN 2 Padang is categorized as stable and fairly stable. 2) The career decisions of 11th-grade students at SMKN 2 Padang are categorized as good. 3) There is a fairly strong relationship between self-confidence and career decisions of 11th-grade students at SMKN 2 Padang. Therefore, it is recommended that the Guidance and Counseling Teacher provide services and materials to enhance Self Confidence and career decisions.